2015
DOI: 10.3176/proc.2015.1.01
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of finite-time correlations on the turbulent mixing in smooth chaotic compressible velocity fields

Abstract: Most theoretical results about turbulent mixing have been obtained for ideal flows that are delta-correlated in time. As is often believed, those ideal flows are, with regard to mixing, very similar to real flows with a finite correlation time. However, recent results show that these two cases may differ considerably. In this article we study the effects of finite correlation time in a chaotic smooth statistically isotropic two-dimensional velocity field. As mixing is predominantly determined by the statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Unfortunately, the exact value for the parameter u, describing the underlying velocity fields, is not available. However, an approximate value can be deduced from general considerations: while for 2-dimensional Kraichnan flows u = 2, in the case of moderate Kubo numbers, values u ∈ [2.2, 2.5] can be expected [19]. While the data are provided here without a proper error analysis, a nearly linear trend implies a qualitative agreement with the theory, and the degree of fluctuations is indicative of the statistical uncertainties.…”
Section: Size-distribution Of Tracer Patches In Incompressible Chaoti...mentioning
confidence: 91%
See 2 more Smart Citations
“…Unfortunately, the exact value for the parameter u, describing the underlying velocity fields, is not available. However, an approximate value can be deduced from general considerations: while for 2-dimensional Kraichnan flows u = 2, in the case of moderate Kubo numbers, values u ∈ [2.2, 2.5] can be expected [19]. While the data are provided here without a proper error analysis, a nearly linear trend implies a qualitative agreement with the theory, and the degree of fluctuations is indicative of the statistical uncertainties.…”
Section: Size-distribution Of Tracer Patches In Incompressible Chaoti...mentioning
confidence: 91%
“…Apart from the evolution time t, this distribution has only one parameter, u, which, in the case of incompressible ideal Kraichnan flows (delta-correlated in time), equals to the dimensionality of the flow. Recently it has been shown that in the case of real flows, this parameter can take slightly larger values [19]. In the case of non-smooth velocity fields, Eq.…”
Section: Size-distribution Of Tracer Patches In Incompressible Chaoti...mentioning
confidence: 99%
See 1 more Smart Citation
“…The case of compressible fields has been studied preliminarily in a technical report [30]; here we use our model to explain the challenging findings of Ref. [10] and provide a qualitative explanation of this phenomenon.…”
mentioning
confidence: 96%
“…(3) has been tabulated in [29, Eq. 2.6.38.4], and derived in [30]; the one of Eq. ( 4) is derived in the Supplementing Material [27].…”
mentioning
confidence: 99%